Pendekatan Bermain dan Edukasi Sebagai Metode Trauma Healing pada Anak Korban Banjir di Matang Cut Kabupaten Aceh Utara - Yarima Melati; Eka Sari, Putri; Fajar Nassriati, Jumaida (INKAMKU : Journal of Community Service, 2026)
Children and adolescents are age groups that are vulnerable to mental health problems in disaster-affected areas due to the loss of a sense of security and the destruction of living environments, play areas, and educational facilities. The floods and landslides that occurred in Aceh on November 24, 2025 caused psychological impacts in the form of trauma, particularly among children and adolescents in Matang Cut Village, North Aceh Regency. This condition encouraged the implementation of a community service program aimed at supporting the recovery of the mental well-being of children and adolescents in the post-disaster period. The activities were carried out using a persuasive approach by grouping participants based on their educational levels, namely kindergarten, elementary school, and junior high school. Each group was guided by a community service team consisting of lecturers in psychiatric nursing, health promotion, and English. The method applied was learning through play using educational game tools, such as flashcards and puzzles for adolescents, as well as coloring activities for younger children. The results showed very positive responses, indicated by the participants’ enthusiasm, motivation, and cheerfulness from the beginning to the end of the activities. All 34 participants attended the activities in full without leaving before completion. As a form of appreciation, active participants were given door prizes in the form of wafers, bread, and milk. This finding emphasizes that educational and recreational activities are highly necessary as part of efforts to address post-disaster trauma, particularly among children and adolescent age groups